Experimental investigations of nanosecond-pulsed Nd:YAG laser beam micromachining on 304 stainless steel. Issue 1 (May 2018) - Behera, Rasmi Ranjan; Sankar, Mamilla Ravi; Baruah, Prahlad Kumar; Sharma, Ashwini Kumar; Khare, Alika
Abstract: The demand for miniaturized components is increasing day by day as their application varies from industry to industry such as biomedical, micro-electro-mechanical system and aerospace. In the present research work, high-quality micro-channels are fabricated on 304 stainless steel by laser beam micromachining process with nanosecond Nd:YAG laser. The laser pulse energy (LPE), scanning speed (SS) and scanning pass number (SP No.) are used as the process parameters, whereas the depth and width of the kerf as well as the surface roughness are used to characterize the micro-channels. It is found that the kerf depth, width and surface roughness decrease with increase in the SS. The kerf depth sharply increases with increase in the SP No. The kerf width is minimum at 30 mJ LPE, 400 µm s ‒1 SS and 10 SP No. The minimum surface roughness is observed at 30 mJ LPE, 500 µm s ‒1 SS and 10 SP No. The oxygen content is found to gradually decrease with the distance from the centre of the micro-channel. Based on the experimental results, optimized input parameters can be offered to control the micro-channel dimensions and improve their surface finish effectively on stainless steel.